Association Between Blood Cadmium Levels and Cognitive Function in Patients with Parkinson’s Disease: A Pilot Study - Richa Choudhary; AK Singh; Shamrendra Narayan; Pradeep Kumar Yadav (Journal of Indian Academy of Forensic Medicine, 2026)
Keeping in mind the neurological toxicity of Cadmium (Cd) and its possible association with Parkinson’s disease (PD), the present study has been designed to explore whether higher blood Cd levels are a risk factor for advanced cognitive deterioration in patients with PD. The aim of this study was to determine the blood Cd level in patients with PD and to investigate whether a higher Cd level is associated with increased incidence of cognitive deterioration in patients with PD. Case-control study, Setting-tertiary medical teaching institute, participants—We studied the serum Cd levels in 98 PD patients and 50 controls and cognitive examination was done with Addenbrooke’s score. The mean concentration of serum Cd was significantly higher in the PD patients, that is, 0.55 µg/L, in comparison to healthy controls with a mean Cd concentration of 0.0072 µg/L. The median interquartile range concentration of blood Cd was 0.40 µg/L. Serum Cd was significantly higher in the PD group. Bivariate correlations were conducted to assess the relationship between Cd levels and Addenbrook’s Cognitive Examination (ACE) scores. Results of the Pearson correlation indicated that there is a significant negative relationship between serum Cd and ACE score ( r (98) = 0.687, p < .001). In our research, serum Cd levels were related to cognitive deterioration in PD. Simultaneously, age, gender, education, occupation, smoking and alcohol status are all related to cognitive functions in PD.